Penerapan Merdeka Belajar Dengan Media Loose Parts Pada Anak Usia Dini - Ririn, Ririn; Yuntina , Lily (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This study aims to test the application of independent learning with loose parts media in early childhood. This research uses a qualitative field method (Field research). The data sources used are Tk Dwi Warna,Paud Al-Mu’awanah,Paud Al-Wathoniyah 51,Paud Semar sakti,Paud Mutiara Hati Pulo Gebang,This research includes observation, interviews, and documentation. Data analysis techniques using Miles and Huberman analysis include data reduction, data presentation, and conclusion drawn.this study shows that the application of Independent Learning with Loose Parts Media in early childhood from the results of Problem Analysis 3 MB Achievement Schools, Problem Solving is Intensive Development 2 has Achieved BSH. Loose media creates unlimited creative possibilities in learning activities and invites children's creativity to work whose usefulness will never run out.Early childhood Already has the readiness to respond to various Educational Simulations provided by parents and the community around them. This research aims to provide the importance to develop "The Application of Independent Learning with Loose Parts Media in Early Childhood".